Little Oxford dictionary, thesaurus, and wordpower guide - edited by Sara Hawker (Oxford University Press, 2003)
The Little Oxford Dictionary, Thesaurus, and Wordpower Guide provides three books in one compact and durable format. It offers the most authoritative and up-to-date coverage of current English, with a dictionary containing over 40,000 words, phrases, and definitions, and a thesaurus with more than 65,000 alternative words. Matching dictionary and thesaurus entries are presented on the same page for quick and easy reference. A unique Wordpower Guide offering a vocabulary builder, lists of frequently misspelled words, and collective nouns for animals and birds helps you to enrich your vocabulary and use the English language more effectively